Satellite data offers new hope for flood-stricken farmers in India - Amarnath, Giriraj; Sikka, Alok (2018)
Climate change magnifies the risk of disasters and increases their costs. As the climate system has warmed, the number of weather-related hazards globally has tripled, and the number of people living in flood-prone areas and cyclone-exposed coastlines has doubled – and this trend is expected to increase. Dr Giriraj Amarnath and Dr Alok Sikka of International Water Management Institute (IWMI), discuss.